2023
DOI: 10.1002/jmv.28909
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset neurodegenerative diseases as long‐term sequelae of SARS‐CoV‐2 infection: A systematic review and meta‐analysis

Abstract: The association between SARS-CoV-2 infection with increased risk for new-onset neurodegenerative diseases remains unclear. Therefore, this meta-analysis aims to elucidate whether new-onset neurodegenerative diseases are long-term sequelae of SARS-CoV-2 infection. PubMed/MEDLINE, CENTRAL, and EMBASE were systematically searched for articles published up to January 10, 2023. A systematic review and meta-analysis were performed to calculate the pooled effect size, expressed as hazard ratios (HR) with correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Other mechanisms that may impact both retina and brain are populations of microglia that reflect specific niches and phases of neurodegenerative disease, infiltration by circulating immune cells, long-term effects of prior infection, and the impact of microbiota on inflammation and nutrient absorption. 65 – 67 Some of these processes may be visible in the retina with new imaging technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms that may impact both retina and brain are populations of microglia that reflect specific niches and phases of neurodegenerative disease, infiltration by circulating immune cells, long-term effects of prior infection, and the impact of microbiota on inflammation and nutrient absorption. 65 – 67 Some of these processes may be visible in the retina with new imaging technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients, respiratory, cardiovascular, immunological, oncological, metabolic, and renal diseases were detected that were either newly developed or only newly detected (not diagnosed or at least noted on medical records) before the acute episode of COVID-19. Others also found new-onset neurodegenerative diseases as long-term sequelae of SARS-CoV-2 infection, pointing towards the need of increased awareness of potential COVID-19-driven onset of different disorders [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have pointed at a possible association between SARS-CoV-2 infection and neurodegeneration, as identified by a rise in the incidence of cognitive decline and parkinsonism in survivors [28,[32][33][34]. A recent imaging study of COVID19+ subjects, including those with mild disease, revealed reductions in grey matter thickness in olfaction-related structures as well as other regions functionally connected to the olfactory cortex [15].…”
Section: Discussionmentioning
confidence: 99%